Mycobacterium avium complex (MAC) isolated from AIDS patients and the criteria required for its implication in disease Complexo Mycobacterium avium (MAC) isolado de pacientes com AIDS e os critérios exigidos para sua implicação em doença - David Jamil Hadad (Revista do Instituto de Medicina Tropical de São Paulo, 1995)
Before the AIDS pandemia, the Mycobacterium avium complex (MAC) was responsible in most cases for the pneumopathies that attack patients with basic chronic pulmonary diseases such as emphysema and chronic bronchitis36. In 1981, with the advent of the acquired immunodeficiency syndrome (AIDS), MAC started to represent one of the most frequent bacterial diseases among AIDS patients, with the disseminated form of the disease being the major clinical manifestation of the infection8. Between January 1989 and February 1991, the Section of Mycobacteria of the Adolfo Lutz Institute, São Paulo, isolated MAC from 103 patients by culturing different sterile and no-sterile processed specimens collected from 2304 patients seen at the AIDS Reference and Training Center and/or Emilio Ribas Infectology Institute. Disseminated disease was diagnosed in 29 of those patients on the basis of MAC isolation from blood and/or bone marrow aspirate. The other 74 patients were divided into categories highly (5), moderately (26) and little suggestive of disease (43) according to the criteria of DAVIDSON (1989)10. The various criteria for MAC isolation from sterile and non-sterile specimens are discussed. Anterior a pandemia de AIDS, o Complexo Mycobacterium avium (MAC) era responsável pela maioria das vezes, por pneumopatias acometendo pacientes com doença pulmonar crônica de base como enfisema e bronquite crônica36. Em 1981, com o advento da síndrome de imunodeficiência adquirida (SIDA), o MAC passou a representar uma das doenças bacterianas mais frequentes em pacientes com esta síndrome, sendo a doença disseminada a principal forma de manifestação clínica da infecção8. Entre Janeiro de 1989 e Fevereiro de 1991, no Setor de Micobactérias do Instituto Adolfo Lutz em São Paulo, o MAC foi isolado de 103 pacientes a partir do cultivo de diferentes espécimes estéreis e não estéreis processados, coletados de 2.304 pacientes atendidos no Centro de Referência e Treinamento AIDS e/ou Instituto de Infectologia Emilio Ribas. A doença disseminada foi diagnosticada em 29 destes, com base no isolamento do MAC a partir do sangue e/ou aspirado de medula óssea. Os outros 74 pacientes foram agrupados nas categorias altamente (5), moderadamente (26) e pouco sugestiva de doença (43) de acordo com os postulados de DAVIDSON (1989)10. Os diferentes critérios para valorizar o seu isolamento de espécimes estéreis e não estéreis são discutidos.